Multifactor Asset Pricing Models - Karpišová, Iveta; Fučík, Vojtěch; Stádník, Bohumil; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
The theme of this bachelor`s thesis is pricing assets with multifactor fundamental pricing models. We cover the theoretical ground of the single-factor model and three multifactor models, the 3-factor Fama and French model, the 4-factor Carhart model and the 5-factor Fama and French model. The practical part aims to evaluate the explanatory power of the models based on the result of their application on the real financial data, the daily price of the 30 assets of the Dow Jones Industrial Average index. The main achievement is the fact that the best performance on an equally weighted portfolio is that of the 4-factor Carhart model, whereas the market capitalization weighted portfolio`s best estimation is gained with the 5-factor Fama and French model. The difference of the explanatory power of the models is dependent on the way one weights his portfolio and this is proven as statistically important based on the data used in the thesis.
Vedoucí práce: Vojtěch Fučík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses